Aloe vera Phytochemicals as Potential Antibacterial Agents Against Multidrug-Resistant Pseudomonas aeruginosa - Awadh Alanazi; Sonia Younas; Muhammad Umer Khan; Zaman Khan; Muharib Alruwaili; Marwa Abdalla; Abualgasim Elgaili Abdalla; Khalid Abosalif; Hasan Ejaz (International Journal of Microbiology)
Multidrug-resistant (MDR) Pseudomonas aeruginosa poses a global challenge due to its high virulence and resistance mechanisms, which lead to persistent infections. This study explored the efficacy of active compounds of Aloe vera as alternative treatments against MDR P. aeruginosa isolates. A total of 283 P. aeruginosa isolates were obtained from sputum and throat samples. The antibiotic resistance of these isolates was evaluated against several antibiotic classes. The minimum inhibitory concentration (MIC) of A. vera–derived phytochemicals was individually assessed; lupeol was found to be a potent phytochemical with the lowest MIC (125 μg/mL). The physicochemical properties and toxicity of the phytochemicals were further evaluated using SwissADME, StopTox, and Protox 3.0. Genetic analysis identified mutations in the AmpC protein as a key factor of antibiotic resistance; consequently, molecular docking studies examined interactions between A. vera phytochemicals and AmpC. Most P. aeruginosa isolates exhibited pronounced antibiotic resistance, while the phytochemicals demonstrated favorable pharmacological properties and strong binding interactions with key amino acids in AmpC. Of these phytochemicals, aloe-emodin showed the most promising antibacterial activity. These findings underscore the potential of A. vera–derived phytochemicals for clinical application as alternative treatments for combating drug-resistant bacterial infections.